Competition Policy as a Strategic Determinant of Economic Development in the Post-pandemic Period: Management and Legal Aspects - Avanesova, Nina; Vovk, Viktoriia; Reshetniak, Natalia; Volosnikova, Nataliia; Yehorova, Yuliia (Universidad de Almería, 2021)
The state and tendencies of COVID-19 influence on the economic situation in the world are studied and the socio-economic losses suffered by the world economy during the pandemic are analyzed. The entire world community, starting in mid-December 2019, has come under the enormous influence of the World Coronavirus Epidemic, called COVID-19. The pandemic caused by this virus has already caused thousands of casualties around the world, imposed significant restrictions on the socio-cultural life of the population and radically changed the trends of the global economy. Today, it is difficult to predict what final human casualties and economic losses will be suffered by states in the short, medium and long term. However, it is important to consider individual economic development forecasts and measures selected by the governments of the world's leading countries to overcome the negative effects of the COVID-19 pandemic. This will allow to form a real vision of the possible course of economic processes that will directly affect the level of socio-cultural life of the population.and the real measures taken to stabilize the financial and economic situation at the micro and macro levels.
Keywords: competition policy; COVID-19 pandemic; coronavirus; Legal regulation; public policy; unemployment; economic management